"Wenn sich die Mitte auflöst...", ist das kein Verlust für die Religionspädagogik - ein bilanzierender Tagungsrückblick mit Augenzwinkern - Uppenkamp, Vera; Höger, Christian (Theo-Web. Zeitschrift für Religionspädagogik)

Art. Mädchen/Frauen - Uppenkamp, Vera (Das wissenschaftlich-religionspädagogische Lexikon im Internet www.wirelex.de)

Systemtheorie von Hardware-in-the-Loop-Simulationen mit Anwendung auf einem Fahrzeugachsprüfstand mit parallelkinematischem Lastsimulator - Olma, Simon

Systematik zur Evolution technischer Anforderungen - Lankeit, Christopher

Das Audioviduum. Eine Theoriegeschichte des Menschenmotivs in audiovisuellen Medien - Eckel, Julia

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

The Public Service Media and Public Service Internet Manifesto

The Future of Public Service Media and the Internet - Alessandro, D'Arma; Fuchs, Christian; Horowitz, Minna; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

Introduction - Fuchs, Christian; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

The Digital Commons and the Digital Public Sphere: How to Advance Digital Democracy Today - Fuchs, Christian (Westminster Papers in Communication and Culture)

How Did Donald Trump Incite a Coup Attempt? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Foundations of Communication/Media/Digital (In)Justice - Fuchs, Christian (Journal of Media Ethics)

Channel 4: Rather Than Privatising Public Service Media We Should Be Expanding It Online - Fuchs, Christian (The Conversation)

Preface: Manfred Knoche’s Critique of the Political Economy of the Media and Communication [Preface to the article “Media Concentration” by Manfred Knoche] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (Crystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials - Tiemann, Michael; Weinberger, Christian (Advanced Materials Interfaces)
Tailor-made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface-area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e. , hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed.

Engels@200: Friedrich Engels in the Age of Digital Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Bewegungsförderung in Ganztagsschulen - Möhring, Julia; Krumhöfner, Anika; Gräfin von Plettenberg, Elisabeth Gudila Sophia Ida Maria (-)

Veranstaltungsbericht: Immaterielles Kulturerbe in Nordrhein-Westfalen – Steigerlied und Trinkhallenkultur im Ruhrgebiet erhalten Auszeichnung anlässlich der Neuaufnahmen in das nordrhein-westfälische Landesinventar - Leineweber, Jonas

Tagungsbericht: Immaterielles Kulturerbe und regionale Identität. Gesellschaftliche Repräsentation und Partizipation im Schützenwesen - Leineweber, Jonas

Lattice parameters and electronic band gap of orthorhombic potassium sodium niobate K0.5Na0.5NbO3 from density-functional theory - Bidaraguppe Ramesh, Nithin; Schmidt, Falko; Schindlmayr, Arno (The European Physical Journal B)
We perform a theoretical analysis of the structural and electronic properties of sodium potassium niobate K1-xNaxNbO3 in the orthorhombic room-temperature phase, based on density-functional theory in combination with the supercell approach. Our results for x=0 and x=0.5 are in very good agreement with experimental measurements and establish that the lattice parameters decrease linearly with increasing Na contents, disproving earlier theoretical studies based on the virtual-crystal approximation that claimed a highly nonlinear behavior with a significant structural distortion and volume reduction in K0.5Na0.5NbO3 compared to both end members of the solid solution. Furthermore, we find that the electronic band gap varies very little between x=0 and x=0.5, reflecting the small changes in the lattice parameters.

Erratum: Efficient implementation of the GW approximation within the all-electron FLAPW method [Phys. Rev. B 81, 125102 (2010)] - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Polaronic enhancement of second-harmonic generation in lithium niobate - Kozub, Agnieszka L.; Schindlmayr, Arno; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)
Density-functional theory within a Berry-phase formulation of the dynamical polarization is used to determine the second-order susceptibility χ(2) of lithium niobate (LiNbO3). Defect trapped polarons and bipolarons are found to strongly enhance the nonlinear susceptibility of the material, in particular if localized at NbV–VLi defect pairs. This is essentially a consequence of the polaronic excitation resulting in relaxation-induced gap states. The occupation of these levels leads to strongly enhanced χ(2) coefficients and allows for the spatial and transient modification of the second-harmonic generation of macroscopic samples.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

Aufgaben und Zuständigkeiten von allgemeinen und sonderpädagogischen Lehrkräften sowie Fachkräften der Schulsozialarbeit in inklusiven Schulen der Sekundarstufe I. Erste Ergebnisse aus dem BiFoKi-Projekt - Neumann, Phillip; Grüter, Sandra; Eckel, Lisa; Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia (Zeitschrift für Heilpädagogik)
Multiprofessionelle Teams sind notwendiger Bestandteil inklusiver Schulen. Die Verteilung von Aufgaben, welche über die Zusammenarbeit von allgemeinen und sonderpädagogischen Lehrkräften im Unterricht hinausgehen, wurde bislang jedoch selten systematisch untersucht. Im Beitrag werden deskriptive Befunde aus dem Projekt BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) zu den Zuständigkeiten von allgemeinen (N = 170) und sonderpädagogischen Lehrkräften (N = 24) sowie Schulsozialarbeiterinnen (N = 11) an inklusiven Sekundar- und Gesamtschulen präsentiert. Sie deuten auf eine Persistenz traditioneller Rollenmuster und Aufgabenverteilungen hin. Bei den befragten sonderpädagogischen Lehrkräften können zwei unterschiedliche Rollenmuster herausgearbeitet werden. Die Schulsozialarbeiterinnen weisen ein enges Arbeitsfeld mit einem Fokus auf Eltern-Schule-Kooperation auf.
Keywords: Inklusion; Sonderpädagogik; Sekundarstufe; Gesamtschulen; Kooperation; Schulsozialarbeit; BiFoKi

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

Malicious Routing: Circumventing Bitstream-level Verification for FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (2021 Design, Automation & Test in Europe Conference & Exhibition (DATE))
The battle of developing hardware Trojans and corresponding countermeasures has taken adversaries towards ingenious ways of compromising hardware designs by circumventing even advanced testing and verification methods. Besides conventional methods of inserting Trojans into a design by a malicious entity, the design flow for field-programmable gate arrays (FPGAs) can also be surreptitiously compromised to assist the attacker to perform a successful malfunctioning or information leakage attack. The advanced stealthy malicious look-up-table (LUT) attack activates a Trojan only when generating the FPGA bitstream and can thus not be detected by register transfer and gate level testing and verification. However, also this attack was recently revealed by a bitstream-level proof-carrying hardware (PCH) approach. In this paper, we present a novel attack that leverages malicious routing of the inserted Trojan circuit to acquire a dormant state even in the generated and transmitted bitstream. The Trojan's payload is connected to primary inputs/outputs of the FPGA via a programmable interconnect point (PIP). The Trojan is detached from inputs/outputs during place-and-route and re-connected only when the FPGA is being programmed, thus activating the Trojan circuit without any need for a trigger logic. Since the Trojan is injected in a post-synthesis step and remains unconnected in the bitstream, the presented attack can currently neither be prevented by conventional testing and verification methods nor by recent bitstream-level verification techniques.

Intermetallic Phases Identification and Diffusion Simulation in Twin-Roll Cast Al-Fe Clad Sheet - Křivská, Barbora; Šlapáková, Michaela; Veselý, Jozef; Kihoulou, Martin; Fekete, Klaudia; Minárik, Peter; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Materials)
Aluminium steel clad materials have high potential for industrial applications. Their mechanical properties are governed by an intermetallic layer, which forms upon heat treatment at the Al-Fe interface. Transmission electron microscopy was employed to identify the phases present at the interface by selective area electron diffraction and energy dispersive spectroscopy. Three phases were identified: orthorhombic Al5Fe2, monoclinic Al13Fe4 and cubic Al19Fe4MnSi2. An effective interdiffusion coefficient dependent on concentration was determined according to the Boltzmann–Matano method. The highest value of the interdiffusion coefficient was reached at the composition of the intermetallic phases. Afterwards, the process of diffusion considering the evaluated interdiffusion coefficient was simulated using the finite element method. Results of the simulations revealed that growth of the intermetallic phases proceeds preferentially in the direction of aluminium.
Keywords: General Materials Science

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Characterization of phase transformations during graded thermo- mechanical treatment of steel 22MnB5 by means of optical methods - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Data for Smart Forming Technologies)

Service life estimation of self‐piercing riveted joints by linear damage accumulation - Masendorf, Lukas; Wächter, Michael; Esderts, Alfons; Otroshi, Mortaza; Meschut, Gerson (Fatigue & Fracture of Engineering Materials & Structures)

Place value and regrouping as seperate constructs of place value understanding - Jensen, Solveig; Gasteiger, Hedwig; Bruns, Julia (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Stellenwertverständnis: Verständnis von Stellenwertprinzip und Bündelungsprinzip als separate Konstrukte - Jensen, Solveig; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2021)

Corona und Krise. Perspektiven erziehungswissenschaftlicher Frauen- und Geschlechterforschung - Mattei, Annalisa; Eremin, Oxana (Bericht zur Jahrestagung der Sektion Frauen- und Geschlechterforschung in der Erziehungswissenschaft in der Deutschen Gesellschaft für Erziehungswissenschaft)

Entwicklungschance oder Warteschleife? Berufsorientierung und Berufswahl in der Berufsfachschule - Schemmer, Susanne Jutta; Heisler, Dietmar; Rink, Julia (Entwicklungen und Perspektiven in der Berufsorientierung. Stand und Herausforderungen. Online: (06.12.2021))

Hochschule auf Abstand
Trotz massiver Förderungen für die Digitalisierung ist die Präsenzlehre noch immer der Standard an deutschen Hochschulen. Aufgrund des Physical Distancing im Zuge der Corona-Pandemie musste sie jedoch kurzfristig fast vollständig digitalisiert werden. Die Beiträge des Bandes bieten einen multiperspektivischen Zugang zu den damit verbundenen Herausforderungen und beleuchten, wie die verschiedenen Akteur*innen die Umstellung auf digitale Lehr- und Lernformate umgesetzt und erlebt haben. Durch die Zusammenführung der verschiedenen Sichtweisen können die Bedarfe und Wünsche der einzelnen Akteursgruppen zusammengebracht und bei der nachhaltigen Weiterentwicklung der Hochschullehre besser berücksichtigt werden.

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

The HighPerMeshes framework for numerical algorithms on unstructured grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz‐Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Concurrency and Computation: Practice and Experience)
Keywords: tet_topic_hpc

Andrea Karimé: Sterne im Kopf und ein unglaublicher Plan. Köln: Peter Hammer Verlag 2021 - Lammer, Christina

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))

Rezension von: Jörg van Norden, Thomas Must, Lars Deile, Peter Riedel, Susan Krause und Wanda Schürenberg (Hgg.): Geschichtsdidaktische Grundbegriffe. Ein Bilderbuch für Studium, Lehre und Beruf. Hannover 2020 - Hartung, Olaf (H-Soz-Kult)

Geometry calibration in wireless acoustic sensor networks utilizing DoA and distance information - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (EURASIP Journal on Audio, Speech, and Music Processing)
Due to the ad hoc nature of wireless acoustic sensor networks, the position of the sensor nodes is typically unknown. This contribution proposes a technique to estimate the position and orientation of the sensor nodes from the recorded speech signals. The method assumes that a node comprises a microphone array with synchronously sampled microphones rather than a single microphone, but does not require the sampling clocks of the nodes to be synchronized. From the observed audio signals, the distances between the acoustic sources and arrays, as well as the directions of arrival, are estimated. They serve as input to a non-linear least squares problem, from which both the sensor nodes’ positions and orientations, as well as the source positions, are alternatingly estimated in an iterative process. Given one set of unknowns, i.e., either the source positions or the sensor nodes’ geometry, the other set of unknowns can be computed in closed-form. The proposed approach is computationally efficient and the first one, which employs both distance and directional information for geometry calibration in a common cost function. Since both distance and direction of arrival measurements suffer from outliers, e.g., caused by strong reflections of the sound waves on the surfaces of the room, we introduce measures to deemphasize or remove unreliable measurements. Additionally, we discuss modifications of our previously proposed deep neural network-based acoustic distance estimator, to account not only for omnidirectional sources but also for directional sources. Simulation results show good positioning accuracy and compare very favorably with alternative approaches from the literature.

Iterative Geometry Calibration from Distance Estimates for Wireless Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

On Source-Microphone Distance Estimation Using Convolutional Recurrent Neural Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

Online Estimation of Sampling Rate Offsets in Wireless Acoustic Sensor Networks with Packet Loss - Chinaev, Aleksej; Enzner, Gerald; Gburrek, Tobias; Schmalenstroeer, Joerg (29th European Signal Processing Conference (EUSIPCO))

A. Seidler, I. Monok (Hgg.): Reformation und Bücher. Zentren der Ideen – Zentren der Buchproduktion. Wiesbaden 2020 - Moritz, Tilman (sehepunkte)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Teilhabe von Eltern an schulischem Lernen mit Family-Literacy-Programmen. Langzeiteffekte von „LIFE – Lesen in Familie erleben“ auf die elterliche Unterstützung beim Lesenlernen - Bonanati, Sabrina; Gruchel, Nicole; Kurock, Ricarda; Buhl, Heike M. (Die Deutsche Schule)
Family-Literacy-Programme stellen eine gute Möglichkeit dar, Eltern in Bildungsprozesse einzubeziehen. Am Beispiel des Programms „LIFE – Lesen in Familie erleben“ wird die Wirkung auf elterliche Unterstützung beim Lesenlernen von Erstklässler*innen unter Einbezug von Eltern- und Kinderperspektive untersucht. Sowohl direkt nach dem Programm als auch ein halbes Jahr später wirkte das Programm positiv auf verschiedene Arten der Anschlusskommunikation beim gemeinsamen Lesen.
Keywords: Kooperation; Familie; Lesekompetenz; Längsschnittstudie; Intervention

Graph-PIT: Generalized Permutation Invariant Training for Continuous Separation of Arbitrary Numbers of Speakers - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Interspeech 2021)
Automatic transcription of meetings requires handling of overlapped speech, which calls for continuous speech separation (CSS) systems. The uPIT criterion was proposed for utterance-level separation with neural networks and introduces the constraint that the total number of speakers must not exceed the number of output channels. When processing meeting-like data in a segment-wise manner, i.e., by separating overlapping segments independently and stitching adjacent segments to continuous output streams, this constraint has to be fulfilled for any segment. In this contribution, we show that this constraint can be significantly relaxed. We propose a novel graph-based PIT criterion, which casts the assignment of utterances to output channels in a graph coloring problem. It only requires that the number of concurrently active speakers must not exceed the number of output channels. As a consequence, the system can process an arbitrary number of speakers and arbitrarily long segments and thus can handle more diverse scenarios. Further, the stitching algorithm for obtaining a consistent output order in neighboring segments is of less importance and can even be eliminated completely, not the least reducing the computational effort. Experiments on meeting-style WSJ data show improvements in recognition performance over using the uPIT criterion.
Keywords: Continuous speech separation; automatic speech recognition; overlapped speech; permutation invariant training

Speeding Up Permutation Invariant Training for Source Separation - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG Conference)

Self-Trained Audio Tagging and Sound Event Detection in Domestic Environments - Ebbers, Janek; Haeb-Umbach, Reinhold (Proceedings of the 6th Detection and Classification of Acoustic Scenes and Events 2021 Workshop (DCASE2021))
In this paper we present our system for the Detection and Classification of Acoustic Scenes and Events (DCASE) 2021 Challenge Task 4: Sound Event Detection and Separation in Domestic Environments, where it scored the fourth rank. Our presented solution is an advancement of our system used in the previous edition of the task.We use a forward-backward convolutional recurrent neural network (FBCRNN) for tagging and pseudo labeling followed by tag-conditioned sound event detection (SED) models which are trained using strong pseudo labels provided by the FBCRNN. Our advancement over our earlier model is threefold. First, we introduce a strong label loss in the objective of the FBCRNN to take advantage of the strongly labeled synthetic data during training. Second, we perform multiple iterations of self-training for both the FBCRNN and tag-conditioned SED models. Third, while we used only tag-conditioned CNNs as our SED model in the previous edition we here explore sophisticated tag-conditioned SED model architectures, namely, bidirectional CRNNs and bidirectional convolutional transformer neural networks (CTNNs), and combine them. With metric and class specific tuning of median filter lengths for post-processing, our final SED model, consisting of 6 submodels (2 of each architecture), achieves on the public evaluation set poly-phonic sound event detection scores (PSDS) of 0.455 for scenario 1 and 0.684 for scenario as well as a collar-based F1-score of 0.596 outperforming the baselines and our model from the previous edition by far. Source code is publicly available at https://github.com/fgnt/pb_sed.

Adapting Sound Recognition to A New Environment Via Self-Training - Ebbers, Janek; Keyser, Moritz Curt; Haeb-Umbach, Reinhold (Proceedings of the 29th European Signal Processing Conference (EUSIPCO))
Recently, there has been a rising interest in sound recognition via Acoustic Sensor Networks to support applications such as ambient assisted living or environmental habitat monitoring. With state-of-the-art sound recognition being dominated by deep-learning-based approaches, there is a high demand for labeled training data. Despite the availability of large-scale data sets such as Google's AudioSet, acquiring training data matching a certain application environment is still often a problem. In this paper we are concerned with human activity monitoring in a domestic environment using an ASN consisting of multiple nodes each providing multichannel signals. We propose a self-training based domain adaptation approach, which only requires unlabeled data from the target environment. Here, a sound recognition system trained on AudioSet, the teacher, generates pseudo labels for data from the target environment on which a student network is trained. The student can furthermore glean information about the spatial arrangement of sensors and sound sources to further improve classification performance. It is shown that the student significantly improves recognition performance over the pre-trained teacher without relying on labeled data from the environment the system is deployed in.

Digital transformation in industry - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Teaching and Learning Materials - Schneider, Jennifer (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Rezension zu: Dräger, Marco: Denkmäler im Geschichtsunterricht Frankfurt am Main 2021. - Fastlabend-Vargas, Daniel (H-Soz-Kult)

Model approaches for closed-loop property control for flow forming - Riepold, Markus; Arian, Bahman; Vasquez, Julian Rozo; Homberg, Werner; Walther, Frank; Trächtler, Ansgar (Advances in Industrial and Manufacturing Engineering)
The implementation of control systems in metal forming processes improves product quality and productivity. By controlling workpiece properties during the process, beneficial effects caused by forming can be exploited and integrated in the product design. The overall goal of this investigation is to produce tailored tubular parts with a defined locally graded microstructure by means of reverse flow forming. For this purpose, the proposed system aims to control both the desired geometry of the workpiece and additionally the formation of strain-induced α′-martensite content in the metastable austenitic stainless steel AISI 304 L. The paper introduces an overall control scheme, a geometry model for describing the process and changes in the dimensions of the workpiece, as well as a material model for the process-induced formation of martensite, providing equations based on empirical data. Moreover, measurement systems providing a closed feedback loop are presented, including a novel softsensor for in-situ measurements of the martensite content.

"Searching for a Belgian culinary identity - Referat von Prof. Dr. Peter Scholliers" (VIDEO) - Huybrechts, Yves; Scholliers, Peter

"Der belgische Symbolismus - Interview mit dem Direktor der Alten Nationalgalerie, Dr. Ralph Gleis" (PODCAST) - Huybrechts, Yves

"Gebaute Träume - Wohnkultur in Flandern und Wallonien" (VIDEO) - Huybrechts, Yves

Geflippte E-Tutor*innenschulungen - Neiske, Iris (Inverted Classroom and beyond 2021 10 Jahre #icmbeyond. Norderstedt)

Building, emptying out, or dreaming? Action structures and space in undergraduates’ metaphors of academic writing - Scharlau, Ingrid; Karsten, Andrea; Rohlfing, Katharina (Journal of Writing Research)
The aim of the present study is to bring new momentum into research on students’ understanding of academic writing. Drawing on the idea that metaphors give insight into implicit conceptions of abstract entities and processes, we developed a detailed and differentiated set of conceptual metaphors that can be used to study student ideas about writing in research, teaching, and interventions. A large sample of undergraduates produced their everyday understanding of writing in short texts beginning with a self-generated metaphor. Based on theories from cognitive linguistics, the conceptual metaphors in their texts were analyzed in terms of their action quality (transitivity) and spatiality (spatial primitives). The undergraduates’ conceptualizations were very heterogeneous. Most metaphors depart strongly from scientific approaches to academic writing within cognitive psychology and sociocultural theory. Roughly half of the metaphors could be collated to one of four metaphor systems. Depending on the desired degree of abstraction or concreteness, conceptual metaphors or metaphor systems can be employed in further studies to illuminate thinking about writing.
Keywords: metaphor analysis; academic writing; transitivity; spatial primitives

Grenzüberschreitung und Distanzierung – Geschlechterforschung in universitären Toiletten - Krollmann, Rabea; Schmidt, Rebecca; Spill, Annika (blog interdisziplinäre geschlechterforschung)

Das Stellarium Gornergrat - Hohmann, Sascha; Gschwind, Stéphane; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (PhyDid B)

Stellarium Gornergrat – A swiss robotic Observatory for Education and Citizen Science - Ekström, Sylvia; Frey, Jonas; Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Riesen, Timm-Emanuel; Ruffieux, Simon; Schlatter, Peter (SPG-Mitteilungen)

Kinder- und Jugendliteratur intermedial. Unterrichtsanregungen und -materialien zum literarischen Lernen im Medienverbund anhand von Emil und die Detektive (Gym/Ge) und Jakob der Lügner (BK); erstellt von Masterstudierenden der Universität Paderborn

Investigations for the Optimization of Visual and Geometrical Properties of Arburg Plastic Freeforming Components - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. Visual and geometrical properties are a major criterion for characterizing the resulting component quality. The aim of this study was to investigate the influences on visual and geometrical properties of APF components depending on process parameters. Initially the focus was on the analysis of the shrinkage behavior of ABS-M30 (Stratasys). On the basis of the results and an existing procedure by the machine manufacturer, an optimized procedure for determining the scaling factors was developed to counteract the shrinkage. With this procedure a higher dimensional accuracy of the components can be achieved. In addition, it was investigated whether an adaption of the form factor based on a mathematical model depending on the component geometry makes sense. The results were transferred into manufacturing guidelines, which allow the user of the APF-technology to optimize process parameters more efficiently.

Comparison of Component Properties and Economic Efficiency of the Arburg Plastic Freeforming and Fused Deposition Modeling - Moritzer, Elmar; Hecker, Felix; Driediger, Christine; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The additive manufacturing process Fused Deposition Modeling (FDM) is established in the industry for many years. A new, similar process to FDM is the Arburg Plastic Freeforming (APF). The main differences between both processes are the form of the starting material (FDM: Filaments, APF: Conventional granulate) and the material deposition during the layer formation (FDM: Melt strand, APF: fine molten droplets). Since the two processes can be used in similar applications, the aim of this study is to compare both processes in a holistic way. Furthermore, the advantages and disadvantages of the processes are to be highlighted. The systematic comparison between a Stratasys 400mc and the Freeformer 200-3X is divided into the areas of component properties, design limitations and economic efficiency. The material ABS-M30 (Stratasys) is used in both processes. The results show comparable component properties regarding mechanical and optical properties but also differences in design limitations and cost efficiency.

Investigation and Modeling of the Residence Time Dependent Material Degradation in the Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. One disadvantage of the APF is the long residence time of the molten material in the plasticizing unit compared to conventional injection moulding. The dosing volume is emptied very slowly due to only discharging fine plastic droplets. As a result, long residence times can be expected, which can lead to thermal degradation of the material. The aim of this study was to develop a model for calculating the residence time of the material in the APF. The residence time of the material in the thermally critical dosing volume is predicted using software developed in-house. The accuracy of the model could be verified by experimental investigations. Finally, the thermal degradation of the material was investigated by analyzing the correlation to the mechanical properties of tensile strength specimens.

Denken mit dem Stift?! – Digitale Visualisierungsprozesse als Zugang zu komplexen wirtschafts- und berufspädagogischen Themenfeldern. - Kückmann, Marie-Ann; Kundisch, Heike (Didaktisierung des Digitalen: Zur Entwicklung berufs- und wirtschaftspädagogischer Studiengänge)

Should I Follow this Model? The Effect of Uncertainty Visualization on the Acceptance of Time Series Forecasts - Leffrang, Dirk; Müller, Oliver (IEEE Workshop on TRust and EXpertise in Visual Analytics)

Laser Sintering Design Guidelines for media transmitting Components - Kletetzka, Ivo; Kummert, Christina; Schmid, Hans-Joachim (Proceedings of the 32nd Annual International Solid Freeform Fabrication Symposium)
In automotive and other fields of application media-carrying components often have complex, flow-optimized geometries and are made of plastics for reasons of weight and cost. Therefore, the laser sintering technology is predestinated to manufacture these components as it offers a very high degree of design freedom and good mechanical properties. For industrial applications the long-term properties of the SLS material in contact with liquid media are important and were therefore investigated for PA12, PP and PA613. Hereby, different media such as motor oil or Glysantin based coolant were tested with different temperatures and immersion times of up to 26 weeks. The mechanical properties were tested after immersion and compared to injection molded samples. Furthermore, laser sintering design guidelines for media-carrying components were developed. These guidelines for instance include the minimum wall thickness to ensure media tightness and the removal of powder from channels with a high length to diameter ratio.

Student engagement in digitalen Lehr-Lern-Szenarien - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)
In diesem Beitrag wird das Konzept des student engagement mit den drei Dimensionen Verhalten, Emotion und Kognition skizziert und in Bezug auf die unterstützenden Faktoren für Lehre auf Distanz in digitalen Lehr-Lernsettings untersucht. Ein Abgleich der theoretischen Grundlagen mit Forschungsergebnissen verschiedener Studien zum Onlinesemester 2020 sowie eine Konkretisierung durch Evaluationen aus Seminaren der englischen Sprachwissenschaft und der Kunstdidaktik gibt Aufschluss darüber, wie ein geeignetes how to engage auch in digitalen Lehr-Lernsettings gelingen kann. Darüber hinaus lassen die Ausführungen erkennen, dass die unterstützenden Faktoren häufig in ähnlich priorisiert werden. Daraus ergibt sich eine Reihenfolge mit dem unterstützenden Umfeld an erster, aktivem und kollaborativem Lernen an zweiter, Erleben von Kompetenz an dritter und akademischer Herausforderung an vierter Stelle. Die Ergebnisse können damit einen Weg aufzeigen, wie auch in ungewohnten Lehr-Lernsettings sukzessive ein geeignetes how to engage entwickelt werden kann, um student engagement zu fördern.

"Unsere Rache ist unsere Existenz. Unsere Waffe ist die Sprache." Zum desintegrativen Potenzial von Mirna Funks Roman "Winternähe" - Spener, Anna Maria (Undercurrents – Forum für linke Literaturwissenschaft)

“Mably on Esteem, Republicanism, and the Question of Human Corruption.” - Blank, Andreas (Journal of Modern Philosophy)

“The Morality of the Desire for Esteem: Gassendi and the Augustinian Challenge.” - Blank, Andreas (History of European Ideas)

“Wolff on Duties of Esteem in the Law of Peoples.” - Blank, Andreas (European Journal of Philosophy)

Die epistemische Dimension der Neuen Rechten. Von einer Kritik des Wissenschafts- und Bildungsverständnisses der Neuen Rechten zu einer Selbstkritik - Haker, Christoph; Otterspeer, Lukas (recht extrem? Dynamiken in zivilgesellschaftlichen Räumen)

Against Latour – On the Questionable Foundations of Post-Critical Pedagogy - Haker, Christoph; Otterspeer, Lukas (On Education. Journal for Research and Debate)
Critique has run out of steam – this diagnosis by Bruno Latour is crucial for the “Manifesto for post-critical education” as well as for the on_education issue “The Fatique of Critique?”. With this essay, we contradict Latour's diagnosis. Latour’s polemic against critique is based firstly on a questionable diagnosis of our time and secondly on a general and programmatic critique of sociology. Against that, we bring out two main points. The first insight highlights that change is initially dependent on variations that can only arise from a negation of the existing. The second insight comes from the sociology of critique, which paradoxically sees success in the failure of critique.

Die Beweglichkeit der Kritik: zur Wechselbeziehung von Kontextualisierung und Objektivierung im digitalen Zeitalter - Haker, Christoph; Otterspeer, Lukas (BEHEMOTH. A Journal on Civilisation)

Digitalisation in the Classroom – Learning Tools - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Fostering Digitisation and Industry 4.0: Education – Vocation – Industry – Future. New Opportunities and Challenges for European VET. Insight in the DigI-VET Project

Higher-rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, L.

Medien der Sorge, Techniken des Selbst. Praktiken des Über-sich-selbst-Schreibens bei Christoph Schlingensief und Elfriede Jelinek - Degeling, Jasmin

Hallo Schönheiten! Performances und Aushandlungen der Geschlechterordnung in der YouTube-Beauty-Community - Richter, Susanne
Keywords: {<}3

Weltweite Verfügbarkeit und digitale Langzeitarchivierung - Ried, Dennis (Mitteilungen der IMRG)

Conference Report: Dynamics of Tradition: Islamic Theology and Law in Relation (September 17-19, 2021, Paderborn) - Nassery, Idris; Tatari, Muna; Mustafa, Abdul Rahman